Confronting the Seismic Impact of COVID-19: The Need For Research - Fischer, Karin (Journal of International Students, 2020)
If I had written this essay in time for its original deadline, it would have been different in tone. Though just a month ago, it was another, now distant time. Back then I would have written about the explosion of international students on American campuses over the past decade and speculated about whether that boom had gone bust. Geopolitical tensions, global competition, visa holdups, nativism, gun violence — all have contributed to softening enrollments, with the number of new international students coming to the United States declining for three years running. But, I would have concluded, colleges are culprits, too, because their practices — including a lack of diversification of student recruitment, a failure to fully integrate international students into campus life, and insufficient investment in career counseling for students from overseas — have at times undermined the experience of international students in the U.S. And that’s a good thing, I would have suggested, because it means that higher education has the power to do something to address the hurdles that international students face. I didn’t make the February 15 deadline for inclusion in the spring issue, however, because I was increasingly pulled away to cover this frightening new respiratory disease and its impact on higher education. Back then, reporting on COVID-19 was a job for the international reporter, with the focus on what was happening abroad and its impact on student and faculty travel and collaboration. In a few short weeks, however, the coronavirus has come home, to the American campus, to America. The pandemic is upending daily life, but its impact could be especially seismic for international education, and one that those in the field have little ability to affect. All of us, everyone reading this journal, are committed to a career of crossing cultures and borders. Now, we’re house-bound. Some international students are stuck in the United States, stranded by travel bans. Others may struggle to get visas to return. Will parents, stunned by the coronavirus’ quick circumnavigation of the globe, be willing to put their children on airplanes and send them to far-away foreign campuses? It is far from clear what next week, next month, next fall, next year will bring. When I speak with some veteran international educators, they remind me of the field’s resiliency and quick rebound after the September 11th terror attacks. Others shake their head. I’ve never seen anything like this, they say. Amid all the uncertainty, one thing I do know: You will help me make sense of it. As a reporter, much of my work, by its nature, is rooted in anecdote. The research community that has built up around the Journal of International Students has helped provide rigor. The studies, both quantitative and qualitative, published here have shed light on the cultural adjustments inbound and outbound students face, given me new ways of conceiving of student identity, and highlighted the impact on labor-market outcomes of studying overseas, to name a few. The work that you do as scholars has informed the work of my readers, many of whom are practitioners, and the examined approach is often a stronger one. We all are apprehensive about international education’s future, but I am encouraged to know that there is a community committed to better understanding it.